Smart Healthcare Monitoring System Using IoT - Mohammed, Bzhar Ghafour; Hasan, Dler Salih (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The progress in communication and information technology has contributed to the creation of the Internet of Thing (IoT). Internet of Things today plays a crucial role in tracking, documenting, storing, presentation and communication in variety of fields like healthcare, smart cities, engineering, and others. Using an IoT-based monitoring system, the critical parameters of health are tracked and data transmitted via network. Data will be accessed for the benefit of the patient’s current condition. This research paper focused on remote monitoring of body temperature (DS18B20), heart rate and SPO2(MAX30100), additionally the position of patient can be obtained on demand using SIM7600E GSM and GNSS HAT (Hardware attached on top) Module. Raspberry Pi 4B used as microcontroller to gather data from health parameter sensors. The data from sensors transmitted into cloud storage through a network. The proposed system uses last version of IoT microcontroller and devices were used which significantly affected the precision and speed of the whole system. A GUI cross platform mobile application was developed for presenting real-time data to both doctors and patients. The system is beneficial for synchronous monitoring of patient’s health status hence allowing urgent medical decision by doctors at right time.